MANEJO DA ADUBAÇÃO NITROGENADA E NUTRIÇÃO COM NITROGÊNIO NA CULTURA DO FEIJÃO IRRIGADO POR PIVÔ CENTRAL - SILVA, D. C.; LOPES, A. S.; SILVA, M. A. C.; CAPRISTO, D. P.; VIEGAS, D. M.; FANAYA JUNIOR, E. D. (ANAIS DO ENIC, 2016)
-